INTERACTIVE MULTIMEDIA LEARNING BASED ADOBE FLASH ON THE SUBJECT OF SYSTEM OF LINEAR EQUATIONS IN TWO VARIABLES - Kurbiyanto R Lapengo; Sumargiyani Sumargiyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Mathematics is one of the science that grow as technology advances. One way to achieve the learning objectives of mathematics learning media is to make an exciting and fun resource in the learning process. The availability of media learning in school is still limited to print media. Teachers have not used multimedia interactive learning lab space, so it is rarely utilized in learning. This research aims to develop research to generate media learning math using adobe flash CS6 in learning mathematics on linear equations in two variables (SPLDV) grade 8 Junior High School. Research development uses the ADDIE model of development through five stages of development: the stage of the analysis, design, development, implementation, and evaluation. The research subject is material expert, media experts, and State Junior High School (SMP Negeri) 1 Kalasan. The instruments used in this is a questionnaire. The data analysis technique was carried out quantitatively and qualitatively to count the score test results of the feasibility study developed media. The research development of interactive multimedia learning-based adobe flash based on the quality of every aspect of the media learning in terms of expert material in categories with a perfect percentage of an average score of 93,33%, in terms of media experts in categories with a significant percentage of an average score of 94,73%, and the response of the students in the category is exciting with a percentage of an average score of 85,84%. Based on the assessment, then interactive multimedia learning-based adobe flash is handy in the learning process.